The Very Possibility of a Science of Religion: Ernst Troeltsch and Neo-Kantianism - Woodford, Peter (The journal of religion, 2017)
The article focuses on the works of philosophers Ernst Troeltsch and Heinrich Rickert and discusses the philosophy of Neo-Kantianism. Topics discussed include the concept of psychologism, the German Idealism, and Rickert's book "Der Gegenstand der Erkenntnis." Also mentioned are the use of sciences in Rickert's works, the relation between sciences and religion, and philosopher Hermann Lotze.